The Influence of Financial Literacy and Financial Behavior on Investment Decision for Young Investor in Badung District, Bali - Kurniadi, Annabella Claudia; Sutrisno, Timotius FCW; Kenang, Irantha Hendrika (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 16 Nomor 2 Tahun 2022, 2022)
Various factors that indicates the increasing rate of investment scam cases are some of which are allegedly due to people who are lack education about finance and investment. The purpose of this research is to find out the influence of Financial Literacy and Financial Behavior as independent variables on Investment Decision as dependent variable with Financial Behavior as well as a mediation variable. The method that is used in this research is an analysis method in the form of Partial Least Square (PLS) with SmartPLS software. The sample of this research is young investors in the age range of 18 to 40 years old who are domiciled in Badung District, Bali as many as 156 respondents. Purposive sampling technique is used with the determination of sample size using Hair formula. Data collection technique in this research is distributing online questionnaires with Likert Scale measurement. Based on data analysis, it is concluded that Financial Literacy and Financial Behavior, influence significant on Investment Decision. Financial Behavior does not provide mediation role as the relation between Financial Literacy and Investment Decision. The result of this research explains that the higher the level of Financial Literacy and the level of Financial Behavior of an investor is, the more helpful investors are in making investment decision.